Minimally Invasive Diagnosis of Secondary Intracranial Lymphoma - A. P. McClement; G. M. Healy; C. E. Redmond; E. Stocker; G. Connaghan; S. J. Skehan; R. P. Killeen (Case Reports in Hematology)
Diffuse large B cell lymphomas (DLBCL) are an aggressive group of non-Hodgkin lymphoid malignancies which have diverse presentation and can have high mortality. Central nervous system relapse is rare but has poor survival. We present the diagnosis of primary mandibular DLBCL and a unique minimally invasive diagnosis of secondary intracranial recurrence. This case highlights the manifold radiological contributions to the diagnosis and management of lymphoma.